2004
DOI: 10.1002/ptr.1440
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid alleviates lipid peroxidation in diabetic rats

Abstract: Diabetes mellitus is a metabolic disorder associated with increased formation of free radicals. The objective of our study was to determine whether ferulic acid (FA), a phenolic acid, has any role to play in diabetes induced free radical formation. Diabetes was induced with streptozotocin. The levels of blood glucose, thiobarbituric acid reactive substances (TBARS), hydroperoxides and free fatty acids (FFA) increased in the liver of diabetic animals. The activities of glutathione peroxidase (GPx), superoxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(151 citation statements)
references
References 19 publications
13
131
0
7
Order By: Relevance
“…Flavonoid and terpenes isolated from the other antidiabetic medicinal plants has been found to stimulate secretion or possess an insulin like-effect [27]. Effect of the flavonoids quercetin and ferulic acid on pancreatic β-cells leading to their proliferation and secretion of more insulin have been proposed by [28,29] as the mechanism by which they reduced hyperglycaemia caused by streptozocin in diabetic rats. The flavonoids present in c may also be acting similarly.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid and terpenes isolated from the other antidiabetic medicinal plants has been found to stimulate secretion or possess an insulin like-effect [27]. Effect of the flavonoids quercetin and ferulic acid on pancreatic β-cells leading to their proliferation and secretion of more insulin have been proposed by [28,29] as the mechanism by which they reduced hyperglycaemia caused by streptozocin in diabetic rats. The flavonoids present in c may also be acting similarly.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that antioxidants ameliorate a number of altered physiological and metaboli c parameters that occur as a result of type-2-diabetes [21,22]. Also in clinical, experimental in vivo and in vitro models of diabetes, antioxidant potential correlates with the degree of glycemic control and it decreases with pro longed diabetes [23].…”
Section: Discussionmentioning
confidence: 99%
“…The sugar beet pulp is an important source of ferulic acid, a phytophenol with antioxidative and anti-inflammatory effects (Couteau et al, 1998). It has been demonstrated that low dosage of cinnamic acids (especially ferulic acid) has been related with the stimulation of insulin secretion (Balasubashini et al, 2003, Adisakwattana et al, 2008, prevention of oxidative stress and lipid peroxidation (Balasubashini et al, 2004, Srinivasan et al, 2007, and inhibition of diabetic nephropathy progression (Fujita et al, 2008). The interaction of select bacteria in the host intestines with dietary fiber, and the possible release of phenolic acids, is an interesting process to be analyzed in order to generate a rationale understanding of the problem.…”
Section: Identification Of Feruloyl Esterases From Bacteriamentioning
confidence: 99%